On the adaptation of the firm’s strategies to the international business environment: a knowledge-based and evolutionary perspective - Ferreira, Manuel Portugal (2021)
This paper discusses the importance of the adaptation of the firm’s strategies to the International Business Environment (IBE). The IBE is a distinguishing factor in international business studies and the firm’s adaptation to the environment has been presented as a basic survival strategy. We argue that adaptation is a dynamic and largely internally driven process that leads the firm to co-evolve with the external environment. The ability to adapt to different international business environments is developed over time through the firm’s experiences and built into its routines and strategies. We suggest that adaptation incorporates the elements of a planned strategy and of random variation in the search for local peaks given bounded rationality, imperfect information and the current pool of resources and capabilities. The ability to adapt to the environment may be conceptualised as a knowledge-based capability and a potential source of competitive advantage for the multinational corporation.